The Influence of the Work Environment and Work Stress on Employee Turnover Intention at PT Selalu Cinta Indonesia Salatiga - Rieke Meilinda; Palupiningtyas, Dyah; Tri Maryani (International Journal of Integrated Science and Technology, 2024)
This study explores the influence of the work environment and work stress on employees' turnover intention. A good work environment and minimal work stress are important factors in keeping employees in the organization. Data was collected from 60 respondents using the Structural Equation Modeling (SEM) research method. The results of the analysis show that the work environment has an insignificant influence on the intention to leave, while work stress has a significant influence. This shows that managing work stress is crucial for organizations to retain employees. The practical implication of these findings is the importance for organizations to identify and reduce factors that can cause work stress, thereby improving employee well-being and overall organizational performance.